An Inventory Model with Lost Sale is Time Dependent - Chen, Ying-Chieh; Chen, Po-Yu (The Economics and Finance Letters, 2014)
In this paper, we shall construct an inventory model with partially backlogged shortage and Poisson demand. In the shortage period, we assume that lost sale is dependent on the length of waiting time. Under these assumptions, we find the optimal planning and shortage periods such that the expected profit per unit time is maximized. Also, we can estimate the optimal expected backordered quantity and the expected order quantity.